PENGARUH GAYA KEPEMIMPINAN PATERNALISTIK DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada PT Pos Indonesia Regional VI Semarang) - Prilly, Adhinda; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2017)
Human resources quality of the company can be measured through employee performance. Employee’s performance is one of factors to achieve the company objectives. The factors that affect employee performance are paternalistic leadership style and organizational culture. This research aimed to analyze the effect of paternalistic leadership style and organizational culture on Employee’s performance with employee engagement as the intervening.This research were done at PT Pos Indonesia Regional VI Semarang. The data collected from 71 respondent by using census. The data were analysed by using double regression by 23th version of SPSS.The Result of this research showed that the effect of paternalistic leadership style and organizational culture on employee engagement (as variable intervening) is positive and significant and the impact of employee engagement on employee’s performance is positive and significant.